2020
DOI: 10.1051/0004-6361/201937035
|View full text |Cite
|
Sign up to set email alerts
|

The subsurface habitability of small, icy exomoons

Abstract: Context. Assuming our Solar System as typical, exomoons may outnumber exoplanets. If their habitability fraction is similar, they would thus constitute the largest portion of habitable real estate in the Universe. Icy moons in our Solar System, such as Europa and Enceladus, have already been shown to possess liquid water, a prerequisite for life on Earth. Aims. We intend to investigate under what thermal and orbital circumstances small, icy moons may sustain subsurface oceans and thus be "subsurface habitable"… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 70 publications
0
9
0
Order By: Relevance
“…Previous studies of extrasolar ocean worlds have suggested that, if planets are cold enough to have icy surfaces, illumination from their host stars does not have a major influence on the maintenance of internal oceans and that internal sources of heat from tidal and radiogenic effects are the main factors that influence the depths to liquid layers (Tjoa et al 2020). Hence, as in , we consider tidal heating and radiogenic heating to be the primary forms of internal heating on cold ocean planets.…”
Section: The Depth To Subsurface Oceans On Cold Ocean Planetsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies of extrasolar ocean worlds have suggested that, if planets are cold enough to have icy surfaces, illumination from their host stars does not have a major influence on the maintenance of internal oceans and that internal sources of heat from tidal and radiogenic effects are the main factors that influence the depths to liquid layers (Tjoa et al 2020). Hence, as in , we consider tidal heating and radiogenic heating to be the primary forms of internal heating on cold ocean planets.…”
Section: The Depth To Subsurface Oceans On Cold Ocean Planetsmentioning
confidence: 99%
“…Here, as in , we refer to ocean-bearing planets with icecovered surfaces as cold ocean planets. Cold ocean planets may be plentiful in extrasolar planetary systems and common throughout the Galaxy (Ehrenreich et al 2006;Ehrenreich & Cassan 2007;Tjoa et al 2020); their interior structures and compositions may resemble those of the large icy moons in our outer solar system (Tajika 2008;Fu et al 2010;Vance et al 2015;Yang et al 2017;Ribas et al 2018;Vance et al 2020;Kane et al 2021). Despite their ice-covered surfaces, these planets may be astrobiologically significant worlds, with habitable environments in subsurface oceans (Heller & Armstrong 2014;Wilhelm et al 2022) or in waterfilled reservoirs perched within their ice shells (e.g., see Fagents et al 2000;Schmidt et al 2011;Muñoz-Iglesias et al 2013;Manga & Michaut 2017;Lesage et al 2020;Chivers et al 2021;Quick et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Exomoons are a new branch of exoplanetary research; these moons beyond our solar system might expand the classical understanding of habitability too. Heller (2020) and Tjoa, Mueller, & van der Tak (2020) showed that for example through tidal heating subsurface oceans could be heated up, so that there could be liquid water even outside the classical habitable zone. A survey that searched in the last years for exomoons was the Hunt for Exomoons by using Kepler (HEK) as described by Kipping, Bakos, Buchhave, Nesvornỳ, & Schmitt (2012).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies investigated this effect (e.g. Alvarado-Montes et al 2017;Zollinger et al 2017), and a few recent studies applied it to known exoplanets (Guimarães & Valio 2018;Martínez-Rodríguez et al 2019;Tokadjian & Piro 2020;Dobos et al 2021). The two most successful exoplanet observation techniques (in terms of the number of new discoveries), the transit and the radial velocity technique, are biased towards detecting close-in planets, however, any moon around these planets can only stay in orbit for a short time (depending on the orbital and physical parameters, typically for less than a few million years).…”
mentioning
confidence: 99%
“…We ignore radiogenic heating which may play a role in some cases, for example in maintaining a subsurface ocean in icy moons (e.g. Tjoa et al 2020).…”
mentioning
confidence: 99%